Is it time for prenatal chromosomal-microarray analysis to all women? A review of the diagnostic yield in structurally normal fetuses. Issue 2 (April 2021) - Daum, Hagit; Stern, Shira; Shkedi-Rafid, Shiri
Abstract : Purpose of review: Chromosomal-microarray analysis (CMA) is the first-tier test in pregnancies with structural malformations. Accumulating data show that pathogenic copy number variants (CNVs) can also be identified in structurally normal fetuses. We set out to summarize the published data on the diagnostic yield of CMA in structurally normal fetuses. Recent findings: Six studies summarize a total of 29, 612 prenatal CMAs performed in structurally normal fetuses. The incidence of highly penetrant pathogenic/likely pathogenic CNVs is 0.4–2.5%. Variability was demonstrated in the timing of CMA testing and type of CNVs classified as pathogenic. The incidence of variants of uncertain significance is 0.4–5.4%. The prevalence of susceptibility loci is 0.3–0.7% when specified, and the incidence of CNVs associated with late onset disease is 0.1%. Summary: With a frequency of abnormal CNVs of 1:40 to 1:250 in structurally normal fetuses, it is recommended that all pregnant women be informed of the possibility to have CMA performed, even in the absence of malformations. Information should also be provided about uncertain and secondary findings.